Propuesta de un plan estratégico de marketing para el taller de pintura Horacio de la ciudad de Loja - Paladines Balcázar, Ximena del Rocío (2016)
This research work called "PROPOSAL FOR A STRATEGIC PLAN FOR MARKETING HORACIO PAINTING WORKSHOP CITY OF LOJA" is focused on developing a marketing plan for growth of the company under study; its development is based on theoretical information marketing planning on data from 15 surveys of 286 internal customers and external customers, and further an interview made the manager. The methodology used concerns the application of different methods and techniques, such as: historical method used to learn the history of the company, deductive method to determine general conclusions based on the information obtained, inductive method helped to obtain information on the service market provided, fearlessness numerical data statistical method of quantitative analysis and analytical method was used to analyze and interpret the results; as well as direct observation techniques, interview and survey; finally to all this the relevant literature review which records the theoretical bases used for the preparation of this thesis adds. Based on the external analysis could build the matrix of external factors, in order to establish the opportunities and threats, assigning a weight to each of them and thus obtaining the following results: (2.20) is a value that reveals the opportunities (1.31) and threats (0.89), therefore it is evident that the company has external problems and is not taking advantage of opportunities in the market. For the preparation of the evaluation matrix of internal factors, the information obtained from the surveys and interviews applied, assigning them equally weighting according to their impact on the strengths and weaknesses, which determined that (2.67) is an amount considered It is indicating that the strengths (2.20) predominates to the weaknesses (0.47); is that the company internally has no relevant problems that prevent their permanence in the market, and normal unwrapping. Finally in this study we proceeded to develop the SWOT matrix to define strengths, weaknesses, opportunities and threats it possible to design the matrix of high impact, by raising the following objectives: 1.) Run an advertising plan in the media more attuned and local circulation, allowing publicize the service offered by the workshop and attract new customers, for which it requires $ 3.340,00; 2.) Make a promotional plan for all customers of the workshop, where it needs $ 1.215,00; 3.) Train staff in order to stay current with technological changes and in turn enhance the effectiveness of activities, with a budget of $ 1,045.00; 4.) Implement an incentive plan for company staff which is assigned a value of $ 1,500.00, for a total of $ 7.100,00 to execute the marketing plan for each goal a goal to meet, tactics, strategy, activities, time and responsible for the target was raised. To finalize the conclusions and recommendations of the project, based on the results obtained during the research process are determined.